Improved Photostability of a CuI Complex by Macrocyclization of the Phenanthroline Ligands. Issue 14 (18th February 2020) - Brandl, Thomas; Kerzig, Christoph; Le Pleux, Loïc; Prescimone, Alessandro; Wenger, Oliver S.; Mayor, Marcel
Abstract: The development of molecular materials for conversion of solar energy into electricity and fuels is one of the most active research areas, in which the light absorber plays a key role. While copper(I)‐bis(diimine) complexes [Cu I (L)2 ] + are considered as potent substitutes for [Ru II (bpy)3 ] 2+, they exhibit limited structural integrity as ligand loss by substitution can occur. In this article, we present a new concept to stabilize copper bis(phenanthroline) complexes by macrocyclization of the ligands which are preorganized around the Cu I ion. Using oxidative Hay acetylene homocoupling conditions, several Cu I complexes with varying bridge length were prepared and analyzed. Absorption and emission properties are assessed; rewardingly, the envisioned approach was successful since the flexible 1, 4‐butadiyl‐bridged complex does show enhanced MLCT absorption and emission, as well as improved photostability upon irradiation with a blue LED compared to a reference complex. Abstract : Rescue Cu I phenanthroline complexes : Like a safety buoy the macrocyclized bisphenanthroline ligand surrounds the Cu I ion and improves the complex's photostability, visible‐light absorptivity, and emission compared to an open analogue (see graphic).